Resin composition for forming phase-separated structure, and method for producing structure including phase-separated structure wherein the invention provides a resin composition for forming phase-separated structures, improving process margins with specific block copolymers A and B in a defined ratio - DAZAI, TAKAHIRO; IINO, SHOTA; MIYAGI, KEN (2025)
The subject of the present invention is to provide a resin composition for forming a phase-separated structure that can improve process margins. The solution of the present invention is a resin composition for forming a phase-separated structure, which contains specific block copolymer A and block copolymer B, where the ratio of L0 (L0 B) of the block copolymer B to L0 (L0 A) of the block copolymer A (L0 B/L0 A) is 0.70 to 1.20.